Application of Anthropometric Data on Redesign of Lightweight Brick-Cutting Tools to Reduce Workers' Musculoskeletal Complaints - I Gede Bawa Susana; I Made Suartika; Gilang Ade Putra (Logic : Jurnal Rancang Bangun dan Teknologi, 2025)
The work of cutting lightweight bricks manually with the help of cutting tools still leaves problems. Unnatural working postures are a form of problems faced by workers. This causes musculoskeletal complaints that have an impact on comfort at work. To overcome this, a redesign of the lightweight brick-cutting tool was carried out using worker anthropometric data. The redesign was carried out on the pedal switch and work chair because this caused complaints from workers. The results of the redesign reduced the musculoskeletal complaints of workers who did lightweight brick-cutting work by an average of 49.36%. This figure was obtained from measurements after working on the old and new tools. The decrease occurred from an average of 62.8 when using the old tool to 31.8 after the intervention. The study results can be used as a guideline for workers doing manual work to create a comfortable and sustainable working atmosphere.